Resin composition and molded article thereof

By using resin compositions containing crystalline propylene/ethylene embedded segments, ethylene polymers, and inorganic filling, the problem of insufficient hardness and rotation length characteristics in automotive components can be solved. Mechanical properties and applicability.

CN119384462APending Publication Date: 2025-01-28PRIME POLYMER CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202380049840.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-06
Filing Date
2023-06-27
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The prior art is difficult to provide a resin composition with excellent balanced and excellent characteristics of hardness and cyclone length for automotive components.

Method used

The resin composition containing a crystalline acryl/ethylene embedded segment, ethylene polymer, and inorganic filling. The specific ingredients include the crystalline propylene/ethylene embedded section of 50-94 mass. Ethylene polymer and inorganic filling of 5 to 25 mass.

Benefits of technology

The hardness and rotation length characteristics of the resin composition are balanced and excellent. The formed molding body has excellent mechanical properties and is suitable for automotive components and other purposes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present invention addresses the problem of providing: a resin composition which has an excellent balance between hardness and rotational flow length characteristics; and a molded article formed from the resin composition. This resin composition contains: 50-94 parts by mass of a crystalline propylene / ethylene block copolymer (A) satisfying specific conditions; 1-25 parts by mass of an ethylene-based polymer (B) having a density of 915-980 kg / m3 and a melt flow rate (190 DEG C, 2.16 kg load) of 0.1-30 g / 10 min; and 5-25 parts by mass of an inorganic filler (C) (wherein the total of the crystalline propylene / ethylene block copolymer (A), the ethylene polymer (B), and the inorganic filler (C) is taken as 100 parts by mass).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a resin composition containing a propylene / ethylene block copolymer and a molded article formed from the resin composition. Background Art

[0002] Polypropylene resin compositions are widely used in various applications such as automobile interior and exterior parts and housings of electric parts because they are easy to mold and the resulting molded products have excellent rigidity and impact resistance.

[0003] For example, Patent Document 1 describes a polypropylene resin composition containing a specific propylene / ethylene block copolymer, an ethylene / butene-1 copolymer elastomer, and an inorganic filler as a resin composition capable of producing a molded product having low gloss and excellent rigidity.

[0004] In addition, in Patent Document 2, a polypropylene resin composition containing a specific polypropylene resin, an ethylene / α-olefin copolymer rubber having a specific density and MFR, and an inorganic filler is described as a resin composition capable of producing a molded body having improved flow mark appearance, excellent toughness, and a good balance between rigidity and surface hardness when the molded body is made.

[0005] Prior art literature Patent Literature Patent Document 1: Japanese Patent Application Publication No. 2007-92049 Patent Document 2: Japanese Patent Application Publication No. 2008-239971 Summary of the invention

[0006] Problems to be solved by the invention However, the emergence of a resin composition having an excellent balance between hardness and swirl length is required as a material for automobile parts such as bumpers, instrument panels, door trims, and pillars.

[0007] An object of the present invention is to provide a resin composition having well-balanced and excellent hardness and swirl length characteristics, and a molded article formed from the resin composition.

[0008] Technical solutions to solve problems The inventors of the present invention have conducted intensive studies to solve the above-mentioned problems and, as a result, have found that the above-mentioned problems can be solved by the following specific resin composition, thereby completing the present invention.

[0009] The present invention relates to, for example, the following [1] to [9].

[0010] [1] A resin composition comprising: 50 to 94 parts by weight of a crystalline propylene / ethylene block copolymer (A) satisfying the following conditions (1) to (3); Density is 915~980kg / m 3 , and 1 to 25 parts by weight of an ethylene polymer (B) having a melt flow rate (MFR) of 0.1 to 30 g / 10 min as measured at a temperature of 190° C. and a load of 2.16 kg, wherein the ethylene polymer (B) is an ethylene homopolymer or a copolymer of ethylene and an α-olefin having 4 to 12 carbon atoms; and Inorganic filler (C) 5 to 25 parts by mass (wherein the total of the crystalline propylene / ethylene block copolymer (A), the ethylene polymer (B) and the inorganic filler (C) is taken as 100 parts by mass).

[0011] Condition (1): A block copolymer composed of a crystalline propylene polymer component and a propylene-based copolymer component, wherein the amount of the propylene-based copolymer component is 10 to 50% by mass, the intrinsic viscosity [η] of the propylene-based copolymer component measured in tetralin at 135°C is 2.0 to 6.0 dl / g, and the proportion of structural units derived from ethylene in the propylene-based copolymer component is 30 to 80 mol%.

[0012] Condition (2): The propylene-based copolymer component includes a copolymer component (EP-1) and a copolymer component (EP-2), The copolymer component (EP-1) contains 40 to 80 mol% of structural units derived from ethylene and has an intrinsic viscosity [η] of 1.5 to 4.0 dl / g as measured in tetralin at 135°C. The copolymer component (EP-2) contains 30 to 50 mol % of structural units derived from ethylene and has an intrinsic viscosity [η] of 5.0 to 10 dl / g as measured in tetralin at 135° C.

[0013] Condition (3): The mass ratio (EP-1 / EP-2) of the copolymer component (EP-1) to the copolymer component (EP-2) is 10 / 1 to 1 / 1.

[0014] [2] The resin composition according to [1], wherein The copolymer component (EP-1) contains 51 to 58 mol% of structural units derived from ethylene. The copolymer component (EP-2) contains 38 to 48 mol% of structural units derived from ethylene.

[0015] [3] The resin composition according to [1] or [2], wherein The crystalline propylene / ethylene block copolymer (A) further satisfies the following conditions (4) to (6).

[0016] Condition (4): The melt flow rate (MFR) measured at a temperature of 230°C and a load of 2.16 kg is 1 to 500 g / 10 min. Condition (5): The melting point measured by differential scanning calorimetry (DSC) is 155 to 170°C.

[0017] Condition (6): Utilization of the above-mentioned crystalline propylene polymer component 13 The isotactic pentad fraction (mmmm fraction) measured by C-NMR is 96.0-99.9%.

[0018] [4] The resin composition according to any one of [1] to [3], wherein The crystalline propylene / ethylene block copolymer (A) further satisfies at least one of the following conditions (7) and (8).

[0019] Condition (7): The difference ΔC2 between the content of the structural unit derived from ethylene in the copolymer component (EP-1) and the content of the structural unit derived from ethylene in the copolymer component (EP-2) is 1.0 to 13 mol%.

[0020] Condition (8): The difference Δη between the intrinsic viscosity [η] of the copolymer component (EP-1) measured in tetralin at 135°C and the intrinsic viscosity [η] of the copolymer component (EP-2) measured in tetralin at 135°C is 5.8 to 8.5 dl / g.

[0021] [5] The resin composition according to any one of [1] to [4], wherein The present invention further comprises 25 parts by mass or less of a copolymer rubber (D) based on 100 parts by mass of the total of the crystalline propylene / ethylene block copolymer (A), the ethylene polymer (B) and the inorganic filler (C), The copolymer rubber (D) is a copolymer of ethylene and an α-olefin having 4 to 12 carbon atoms and has a density of 850 to 910 kg / m 3 , the melt flow rate (MFR) measured at a temperature of 190°C and a load of 2.16 kg is greater than 0.2 g / 10 min and less than 40 g / 10 min.

[0022] [6] A molded article formed from the resin composition according to any one of [1] to [5].

[0023] [7] The molded article according to [6], which is an injection molded article.

[0024] [8] The molded article according to [6], which is an automobile part.

[0025] [9] The molded article according to [8], wherein the automobile part is a bumper.

[0026] Effects of the Invention According to the present invention, it is possible to provide a resin composition having well-balanced and excellent hardness and swirl length characteristics, and a molded article formed of the resin composition. DETAILED DESCRIPTION

[0027] The present invention will be described in more detail below.

[0028] [Resin composition] The resin composition of the present invention is a resin composition comprising a crystalline propylene / ethylene block copolymer (A), an ethylene polymer (B) and an inorganic filler (C). In one embodiment, the resin composition further comprises a copolymer rubber (D).

[0029] <Crystalline propylene / ethylene block copolymer (A)> The crystalline propylene / ethylene block copolymer (A) according to the present invention satisfies all of the following conditions (1) to (3), preferably further satisfies one or more of the following conditions (4) to (6), and more preferably further satisfies all of the following conditions (4) to (6).

[0030] Condition (1): A block copolymer composed of a crystalline propylene polymer component and a propylene-based copolymer component, wherein the amount of the propylene-based copolymer component is 10 to 50% by mass, the intrinsic viscosity [η] of the propylene-based copolymer component measured in tetralin at 135°C is 2.0 to 6.0 dl / g, and the proportion of structural units derived from ethylene in the propylene-based copolymer component is 30 to 80 mol%.

[0031] In the crystalline propylene / ethylene block copolymer (A) of the present invention, the crystalline propylene polymer component is a component composed of structural units derived from propylene alone, or a component composed of structural units derived from propylene and a small amount of structural units derived from ethylene, and it is considered that it has crystallinity and exhibits rigidity. In the crystalline propylene / ethylene block copolymer (A), the crystalline propylene polymer component can be used as a 23°C n-decane insoluble portion (D insol )extract.

[0032] The amount of the crystalline propylene polymer component in the crystalline propylene / ethylene block copolymer (A) is 50 to 90% by mass, preferably 60 to 90% by mass, more preferably 65 to 85% by mass, and particularly preferably 75 to 83% by mass. The total amount of the crystalline propylene polymer component and the propylene-based copolymer component is 100% by mass. In the present invention, the amounts of the crystalline propylene polymer component and the propylene-based copolymer component are values ​​measured by the method used in the examples described below.

[0033] In the crystalline propylene / ethylene block copolymer (A) involved in the present invention, the propylene copolymer component is a component composed of structural units derived from propylene and structural units derived from ethylene, and is a component that does not show crystallinity or has low crystallinity. It can be considered that it has a low glass transition temperature, shows impact resistance, and shows compatibility with other polymers when mixed with other polymers. It can also be said to be a rubber component. In the crystalline propylene / ethylene block copolymer (A), the propylene copolymer component can be used as a 23°C n-decane soluble portion (D sol )extract.

[0034] The amount of the propylene copolymer component in the crystalline propylene / ethylene block copolymer (A) is 10 to 50% by mass, preferably 10 to 40% by mass, and more preferably 15 to 35% by mass. When the amount of the propylene copolymer component in the crystalline propylene / ethylene block copolymer (A) is less than the lower limit of the above range, there is a tendency for the impact resistance of the molded article obtained from the resin composition containing the copolymer to decrease. It can be considered that this is because the proportion of the propylene copolymer component is reduced, and thus the absorption energy of the crystalline propylene / ethylene block copolymer (A) to impact is reduced.

[0035] On the other hand, when the amount of the propylene-based copolymer component in the crystalline propylene / ethylene block copolymer (A) exceeds the upper limit of the above range, the high-speed moldability of the resin composition containing the copolymer may deteriorate, and the rigidity (yield strength) of the molded product obtained from the resin composition may deteriorate.

[0036] The intrinsic viscosity [η] of the propylene copolymer component measured in tetralin at 135°C is 2.0 to 6.0 dl / g, preferably 2.5 to 6.0 dl / g, more preferably 3.0 to 5.0 dl / g, further preferably 3.1 to 4.5 dl / g, particularly preferably 3.2 to 4.0 dl / g.

[0037] When the intrinsic viscosity exceeds the upper limit of the above range or is lower than the lower limit, the impact resistance of a molded article obtained from the resin composition may decrease.

[0038] The above-mentioned intrinsic viscosity value is a value measured by a method used in Examples described later.

[0039] The ratio of the structural unit derived from ethylene in the propylene-based copolymer component is 30 to 80 mol%, preferably 35 to 60 mol%, more preferably 40 to 55 mol%, and particularly preferably 45 to 54 mol%. The total of the structural unit derived from propylene and the structural unit derived from ethylene in the propylene-based copolymer component is 100 mol%.

[0040] When the ratio of the above-mentioned structural unit from ethene is lower than the lower limit of above-mentioned scope, there is the tendency of the impact resistance variation of the molded product obtained by resin combination. It can be considered that this is because the ethylene content of the propylene copolymer component reduces, thereby the glass transition temperature reduces, the crystallinity increases, and the absorption energy of impact is reduced. In addition, when the ratio of the above-mentioned structural unit from ethene exceeds the upper limit of above-mentioned scope, the moldability variation of resin combination at high speed sometimes.

[0041] The ratio of the structural unit derived from ethylene in the propylene-based copolymer component is a value measured by the method used in the examples described later.

[0042] Condition (2) : The propylene-based copolymer component comprises a copolymer component (EP-1) and a copolymer component (EP-2), The copolymer component (EP-1) contains 40 to 80 mol% of structural units derived from ethylene and has an intrinsic viscosity [η] of 1.5 to 4.0 dl / g as measured in tetralin at 135°C. The copolymer component (EP-2) contains 30 to 50 mol % of structural units derived from ethylene and has an intrinsic viscosity [η] of 5.0 to 10 dl / g as measured in tetralin at 135° C.

[0043] That is, the propylene-based copolymer component in the crystalline propylene / ethylene block copolymer (A) of the present invention comprises: a copolymer component (EP-1) having 40 to 80 mol% of structural units derived from ethylene and having an intrinsic viscosity [η] of 1.5 to 4.0 dl / g as measured in tetralin at 135°C; and a copolymer component (EP-2) having 30 to 50 mol% of structural units derived from ethylene and having an intrinsic viscosity [η] of 5.0 to 10 dl / g as measured in tetralin at 135°C.

[0044] The content of the structural unit derived from ethylene in the copolymer component (EP-1) is 40 to 80 mol%, preferably 45 to 70 mol%, more preferably 50 to 60 mol%, and particularly preferably 51 to 58 mol%. The content of the structural unit derived from propylene and the content of the structural unit derived from ethylene in the copolymer component (EP-1) are taken as 100 mol%. When the content of the structural unit derived from ethylene in the copolymer component (EP-1) exceeds the upper limit of the above range, the rigidity or hardness may become insufficient. In addition, when the content of the structural unit derived from ethylene in the copolymer component (EP-1) is lower than the lower limit of the above range, the impact resistance may become insufficient.

[0045] The intrinsic viscosity [η] of the copolymer component (EP-1) measured in tetralin at 135°C is 1.5 to 4.0 dl / g, preferably 1.8 to 3.5 dl / g, and more preferably 2.0 to 3.0 dl / g. When the intrinsic viscosity [η] of the copolymer component (EP-1) exceeds the upper limit of the above range, the melt flowability of the resin composition may decrease and the moldability may deteriorate. On the other hand, when the intrinsic viscosity [η] of the copolymer component (EP-1) is lower than the lower limit of the above range, the rigidity or hardness of the molded body of the resin composition may become insufficient, or the toughness or impact resistance may become insufficient.

[0046] The content of the structural unit derived from ethylene in the copolymer component (EP-2) is 30 to 50 mol%, preferably 35 to 50 mol%, more preferably 38 to 48 mol%, and particularly preferably 40 to 47 mol%. The content of the structural unit derived from propylene and the content of the structural unit derived from ethylene in the copolymer component (EP-2) are taken as 100 mol%. When the content of the structural unit derived from ethylene in the copolymer component (EP-2) exceeds the upper limit of the above range or is less than the lower limit, the rigidity or impact resistance may become insufficient.

[0047] The intrinsic viscosity [η] of the copolymer component (EP-2) measured in tetralin at 135°C is 5.0 to 10 dl / g, preferably 6.0 to 10 dl / g, more preferably 7.0 to 10 dl / g, further preferably 8.0 to 9.9 dl / g, and particularly preferably 8.5 to 9.8 dl / g. When the intrinsic viscosity [η] of the copolymer component (EP-2) exceeds the upper limit of the above range, the homogeneity of the resin composition may be deteriorated, and a molded article formed from the resin composition may have unevenness on the surface, or mechanical properties such as rigidity may be deteriorated.

[0048] Condition (3) : The mass ratio (EP-1 / EP-2) of the copolymer component (EP-1) to the copolymer component (EP-2) is 10 / 1 to 1 / 1.

[0049] The mass ratio (EP-1 / EP-2) of the copolymer component (EP-1) to the copolymer component (EP-2) is preferably 8 / 1 to 2 / 1, more preferably 6 / 1 to 3 / 1.

[0050] When the mass ratio (EP-1 / EP-2) exceeds the upper limit of the above range, the balance between rigidity and impact resistance of the molded product formed from the resin composition may be deteriorated. When the mass ratio (EP-1 / EP-2) is lower than the lower limit of the above range, the fluidity of the resin composition may decrease, which may lead to poor molding.

[0051] Condition (4): The melt flow rate (MFR) measured at a temperature of 230°C and a load of 2.16 kg is 1 to 500 g / 10 min.

[0052] The melt flow rate (MFR, 230°C, 2.16 kg load) of the crystalline propylene / ethylene block copolymer (A) is preferably 10 to 300 g / 10 min, more preferably 20 to 150 g / 10 min, further preferably 30 to 120 g / 10 min, particularly preferably 40 to 70 g / 10 min.

[0053] When the MFR exceeds the upper limit of the above range, burrs may be generated when the resin composition is injection molded, while when the MFR is below the lower limit of the above range, the fluidity of the resin composition may decrease and the moldability may deteriorate.

[0054] Condition (5) The melting point measured by differential scanning calorimetry (DSC) is 155-170°C.

[0055] The melting point (Tm) of the crystalline propylene / ethylene block copolymer (A) is preferably 158 to 168°C, more preferably 160 to 165°C.

[0056] The melting point (Tm) can be determined specifically by measuring using a differential scanning calorimeter (DSC) under the following conditions in accordance with JIS K7121, and defining the temperature at the top of the third endothermic peak as the melting point. When there are multiple endothermic peaks, the temperature at the top of the largest endothermic peak is defined as the melting point.

[0057] (Measurement conditions) Atmosphere: Nitrogen atmosphere Sample size: 5 mg Sample shape: pressed film (molded at 230°C, thickness 200-400μm) Stage 1: Raise the temperature from 30°C to 240°C at a rate of 10°C / min and hold for 10 minutes.

[0058] Stage 2: Cool down to 60°C at 10°C / min.

[0059] Stage 3: Raise the temperature to 240°C at 10°C / min.

[0060] Condition (6) : Utilization of the above crystalline propylene polymer component 13 The isotactic pentad fraction (mmmm fraction) measured by C-NMR is 96.0-99.9%.

[0061] The details of the measurement conditions and the like are as described in the examples described later. The isotactic pentad fraction (mmmm fraction) is preferably 97.0 to 99.9%, more preferably 97.6 to 99.9%.

[0062] When the crystalline propylene / ethylene block copolymer (A) of the present invention satisfies condition (6), the stereoregularity of the crystalline propylene polymer component is high, and thus the crystallinity increases during crystallization. Therefore, a molded article formed from the resin composition tends to have high rigidity, which is preferred.

[0063] The crystalline propylene / ethylene block copolymer (A) according to the present invention preferably further satisfies at least one of the following conditions (7) and (8), and more preferably satisfies both of the conditions (7) and (8).

[0064] Condition (7): The difference ΔC2 between the content of the structural unit derived from ethylene in the copolymer component (EP-1) and the content of the structural unit derived from ethylene in the copolymer component (EP-2) is preferably 1.0 to 13 mol %, more preferably 3.5 to 11 mol %.

[0065] When the crystalline propylene / ethylene block copolymer (A) according to the present invention satisfies the condition (7), it is preferred because it has an excellent balance between room-temperature impact resistance and low-temperature impact resistance.

[0066] Condition (8): The difference Δη between the intrinsic viscosity [η] of the copolymer component (EP-1) measured in tetralin at 135°C and the intrinsic viscosity [η] of the copolymer component (EP-2) measured in tetralin at 135°C is preferably 5.0 to 8.5 dl / g, more preferably 5.8 to 8.5 dl / g, and even more preferably 6.3 to 8.0 dl / g.

[0067] When the crystalline propylene / ethylene block copolymer (A) according to the present invention satisfies the condition (8), it is preferred because both improvement in appearance and improvement in surface impact resistance can be achieved.

[0068] <Method for producing crystalline propylene / ethylene block copolymer (A)> The crystalline propylene / ethylene block copolymer (A) used in the present invention is preferably produced, for example, by the following method, which sequentially comprises: a step (1) of polymerizing propylene to produce a crystalline propylene polymer component (1); a step (2) of copolymerizing propylene and ethylene in the presence of the crystalline propylene polymer component (1) to produce a copolymer component (EP-1); and a step (3) of copolymerizing propylene and ethylene in the presence of the crystalline propylene polymer component (1) and the copolymer component (EP-1) to produce a copolymer component (EP-2).

[0069] In the steps (1), (2) and (3), propylene homopolymerization or propylene and ethylene copolymerization is usually carried out in the presence of a catalyst containing a metallocene compound or in the presence of a Ziegler-Natta catalyst, preferably in the presence of a Ziegler-Natta catalyst.

[0070] When the polymerization is carried out in the presence of a Ziegler-Natta catalyst, a crystalline propylene / ethylene block copolymer (A) having a wide molecular weight distribution and good moldability can be easily obtained.

[0071] (Catalyst containing metallocene compound) As the catalyst containing the metallocene compound, a metallocene catalyst composed of a metallocene compound, an organic metal compound, an organic aluminum compound, and a compound capable of reacting with a metallocene compound to form an ion pair, and a granular carrier as required can be cited, and a metallocene catalyst capable of stereoregular polymerization such as isotactic polymerization is preferably cited. Among the above-mentioned metallocene compounds, the crosslinking metallocene compounds exemplified in International Publication No. 01 / 27124, the metallocene compounds described in

[0068] to

[0076] of International Publication No. 2010 / 74001, and the like are preferred. In addition, as the organic metal compound, the organic aluminum compound, the compound capable of reacting with a transition metal compound to form an ion pair, and the granular carrier used as required, the compounds disclosed in International Publication No. 01 / 27124, Japanese Patent Publication No. 11-315109, and the like can be used without limitation.

[0072] (Ziegler Natta catalyst) The propylene block copolymer can be produced using a high stereoregularity Ziegler-Natta catalyst. As the above-mentioned high stereoregularity Ziegler-Natta catalyst, various known catalysts can be used. For example, a catalyst composed of (a) a solid titanium catalyst component containing magnesium, titanium, a halogen and an electron donor, (b) an organic metal compound catalyst component and (c) an organic silicon compound catalyst component having at least one group selected from cyclopentyl, cyclopentenyl, cyclopentadienyl and their derivative groups can be used. The catalyst component can be produced according to a known method, for example, the method described in

[0078] to

[0094] of International Publication No. 2010 / 74001.

[0073] When propylene is polymerized using the catalyst composed of the solid titanium catalyst component (a), the organometallic compound catalyst component (b) and the organosilicon compound catalyst component (c), prepolymerization may be performed in advance. In the prepolymerization, olefin is polymerized in the presence of the solid titanium catalyst component (a), the organometallic compound catalyst component (b) and, if necessary, the organosilicon compound catalyst component (c).

[0074] As the olefin to be prepolymerized, α-olefins having 2 to 8 carbon atoms can be used. Specifically, linear olefins such as ethylene, propylene, 1-butene, and 1-octene; olefins having branched structures such as 3-methyl-1-butene, 3-methyl-1-pentene, 3-ethyl-1-pentene, 4-methyl-1-pentene, 4-methyl-1-hexene, 4,4-dimethyl-1-hexene, 4,4-dimethyl-1-pentene, 4-ethyl-1-hexene, and 3-ethyl-1-hexene can be used. These can also be copolymerized.

[0075] The prepolymerization is preferably carried out in such a manner that about 0.1 to 1000 g, preferably about 0.3 to 500 g, of polymer is produced relative to 1 g of the solid titanium catalyst component (a). When the amount of prepolymerization is too large, the production efficiency of the (co)polymer in the main polymerization may decrease. In the prepolymerization, a catalyst having a concentration much higher than that in the main polymerization system may be used.

[0076] In the main polymerization, the amount of the solid titanium catalyst component (a) (or prepolymerized catalyst) used is preferably about 0.0001 to 50 mmol, preferably about 0.001 to 10 mmol, converted to titanium atoms per 1 L of polymerization volume. The amount of the organometallic compound catalyst component (b) used is preferably about 1 to 2000 mol, preferably about 2 to 500 mol, relative to 1 mol of titanium atoms in the polymerization system when converted to the amount of metal atoms. The amount of the organosilicon compound catalyst component (c) used is preferably about 0.001 to 50 mol, preferably about 0.01 to 20 mol, relative to 1 mol of metal atoms in the organometallic compound catalyst component (b).

[0077] The polymerization may be carried out by any method such as gas phase polymerization or liquid phase polymerization such as solution polymerization or suspension polymerization, and step (1), step (2) and step (3) may be carried out by their respective methods. Furthermore, the polymerization may be carried out by any method such as continuous or semi-continuous, or the above steps may be carried out by dividing into a plurality of polymerization vessels, for example, 2 to 10 polymerization vessels. It is most preferable to carry out the polymerization by a continuous method in industrial terms.

[0078] As the polymerization medium, an inactive hydrocarbon can be used, and liquid propylene can be used as the polymerization medium. In addition, the polymerization conditions of each stage can be appropriately selected within the range of a polymerization temperature of about -50 to +200°C, preferably about 20 to 100°C, and a polymerization pressure of normal pressure to 10 MPa (gauge pressure), preferably about 0.2 to 5 MPa (gauge pressure).

[0079] In the production method of the present invention, for example, step (1), step (2) and step (3) are continuously carried out using a reaction apparatus in which three or more polymerization reactors are connected in series. Step (1) may be carried out in each polymerization reactor using a polymerization apparatus in which two or more reactors are connected in series, step (2) may be carried out in each polymerization reactor using a polymerization apparatus in which two or more reactors are connected in series, and step (3) may be carried out in each polymerization reactor using a polymerization apparatus in which two or more reactors are connected in series.

[0080] Step (1) is a step of polymerizing propylene and optionally ethylene at a polymerization temperature of 0 to 100°C and a polymerization pressure of normal pressure to 5 MPa gauge pressure, and is a step of producing a crystalline propylene polymer component (1) by not supplying ethylene or supplying ethylene in a smaller amount than the feed amount of propylene. The crystalline propylene polymer component (1) is a portion showing crystallinity in the crystalline propylene / ethylene block copolymer (A) and can be used as a portion (D) insoluble in 23°C n-decane. insol ) is extracted from the crystalline propylene / ethylene block copolymer (A), and is generally a component mainly composed of structural units derived from propylene, and is considered to have crystallinity and show high rigidity.

[0081] Furthermore, a chain transfer agent such as hydrogen gas may be introduced as necessary to adjust the intrinsic viscosity [η] of the crystalline propylene polymer component (1) produced in the step (1).

[0082] Step (2) and step (3) are steps for producing a propylene-based copolymer component, wherein step (2) is a step for producing a copolymer component (EP-1), and step (3) is a step for producing a copolymer component (EP-2). In the present invention, the propylene-based copolymer component is composed of a copolymer component (EP-1) and a copolymer component (EP-2). The propylene-based copolymer component is a component that does not show crystallinity or has low crystallinity in the crystalline propylene / ethylene block copolymer (A) and can be used as a portion (D ) soluble in 23°C n-decane. sol ) is extracted from the crystalline propylene / ethylene block copolymer (A), and is generally a component mainly composed of structural units derived from propylene and ethylene. It is believed that the propylene copolymer component has a low glass transition temperature, exhibits impact resistance, and exhibits compatibility with other polymers when mixed with other polymers. It can also be said to be a rubber component.

[0083] Step (2) is a step of copolymerizing propylene and ethylene in the presence of a crystalline propylene polymer component (1) at a polymerization temperature of 0 to 100° C. and a polymerization pressure of normal pressure to 5 MPa gauge pressure, wherein the ratio of the amount of ethylene fed to the amount of propylene fed is made larger than that in step (1), thereby producing a copolymer component (EP-1) in the propylene-based copolymer component which is a component having no or low crystallinity.

[0084] Furthermore, a chain transfer agent such as hydrogen gas may be introduced as necessary to adjust the intrinsic viscosity [η] of the copolymer component (EP-1).

[0085] Step (3) is a step of copolymerizing propylene and ethylene at a polymerization temperature of 0 to 100° C. and a polymerization pressure of normal pressure to 5 MPa gauge pressure in the presence of the crystalline propylene polymer component obtained in step (1) and the copolymer component (EP-1) obtained in step (2). This step is a step of producing the copolymer component (EP-2) in the propylene-based copolymer component which is a component having no crystallinity or low crystallinity.

[0086] Since the amount of the propylene copolymer component in the crystalline propylene / ethylene block copolymer (A) in condition (1) is the ratio (mass %) of the crystalline propylene polymer component (1) to the total of the crystalline propylene polymer component (1) and the propylene copolymer component (the total of the copolymer component (EP-1) and the copolymer component (EP-2)), it can be adjusted, for example, by adjusting the polymerization time of each step. That is, by increasing the ratio of the polymerization time of step (2) and step (3) to the total polymerization time, the amount of the propylene copolymer component can be increased.

[0087] The ethylene content in condition (1) or (2) can be adjusted by adjusting the ratio of the ethylene feed amount to the propylene feed amount during step (2) or step (3), respectively. That is, by increasing the feed ratio, the ethylene content can be increased, and by decreasing the feed ratio, the ethylene content can be decreased.

[0088] The intrinsic viscosity [η] in condition (1) or (2) can be adjusted by the feed amount of hydrogen used as a chain transfer agent when performing step (2) or step (3), respectively. That is, by increasing the ratio of the feed amount of hydrogen to the feed amount of monomers (i.e., propylene and ethylene), the intrinsic viscosity [η] can be reduced; by decreasing the ratio of the feed amount of hydrogen to the feed amount of monomers, the intrinsic viscosity [η] can be increased.

[0089] The mass ratio (EP-1 / EP-2) of the copolymer component (EP-1) to the copolymer component (EP-2) in condition (3) can be adjusted, for example, by adjusting the polymerization time of each step. That is, by increasing the ratio of the polymerization time of step (2) to the total polymerization time, the mass ratio (EP-1 / EP-2) can be increased. In addition, by increasing the ratio of the polymerization time of step (3) to the total polymerization time, the mass ratio (EP-1 / EP-2) can be reduced.

[0090] Conditions (4) and (5), i.e., the MFR and melting point of the crystalline propylene / ethylene block copolymer (A) can be adjusted by adjusting the ratio of the amount of hydrogen fed as a chain transfer agent to the amount of monomers (i.e., propylene in the case of propylene homopolymerization, and propylene and ethylene in the case of copolymerization) fed during the steps (1) to (3). That is, by increasing the ratio, the MFR can be increased and the melting point can be decreased; by decreasing the ratio, the MFR can be decreased and the melting point can be increased.

[0091] The condition (6), namely the melting point of the crystalline propylene / ethylene block copolymer (A) and the isotactic pentad fraction (mmmm fraction) of the crystalline propylene polymer component, can be adjusted by adjusting the catalyst and external donor system used in the polymerization.

[0092] After completion of the polymerization, a post-treatment step such as a known catalyst deactivation treatment step, a catalyst residue removal step, a drying step, etc. may be performed as necessary.

[0093] According to such a production method, a crystalline propylene / ethylene block copolymer (A) suitable for a resin composition capable of obtaining a molded product having excellent appearance and impact resistance can be produced. The reason for this is not yet clear, but it is considered that the low molecular weight polymerized rubber component having a high content of structural units derived from ethylene and excellent impact modification performance and the high molecular weight polymerized rubber component having excellent appearance improvement effect are well dispersed at the polymerized powder stage, and their effects are exhibited.

[0094] In addition, the crystalline propylene / ethylene block copolymer (A) of the present invention may contain a structural unit derived from biomass-derived propylene and / or a structural unit derived from biomass-derived ethylene. Furthermore, it may also contain a structural unit derived from chemically recovered propylene and / or a structural unit derived from chemically recovered ethylene. The monomers (propylene and / or ethylene) constituting the polymer may be only a monomer derived from biomass (propylene and / or ethylene), only a monomer derived from chemically recovered (propylene and / or ethylene), only a monomer derived from fossil fuels (propylene and / or ethylene), both a monomer derived from biomass (propylene and / or ethylene) and a monomer derived from fossil fuels (propylene and / or ethylene), both a monomer derived from biomass (propylene and / or ethylene) and a monomer derived from chemically recovered (propylene and / or ethylene), both a monomer derived from biomass (propylene and / or ethylene) and a monomer derived from chemically recovered (propylene and / or ethylene), or all of a monomer derived from biomass (propylene and / or ethylene), a monomer derived from chemically recovered (propylene and / or ethylene), and a monomer derived from fossil fuels (propylene and / or ethylene).

[0095] Biomass-derived propylene and biomass-derived ethylene are monomers obtained from so-called renewable natural raw materials such as plants or animals, including fungi, yeast, algae, and bacteria, and their residues. -12 The 14C isotope is contained in an amount of about 100, and the biomass-based carbon concentration (pMC) measured in accordance with ASTM D6866 is about 100 (pMC). Biomass-derived propylene and biomass-derived ethylene can be obtained by, for example, conventionally known methods.

[0096] From the viewpoint of reducing environmental burden, it is preferred that the crystalline propylene / ethylene block copolymer (A) contains a structural unit derived from biomass-derived propylene and / or a structural unit derived from biomass-derived ethylene. If the polymerization catalyst, polymerization temperature and other polymer production conditions are the same, even if the raw material propylene is a propylene-based block copolymer containing biomass-derived propylene and / or biomass-derived ethylene, except for the 1×10 -12 The molecular structure is the same as that of a propylene / ethylene block polymer composed of fossil fuel-derived propylene and fossil fuel-derived ethylene, except that the 14C isotope is contained in a ratio of about 1.5, and therefore, the performance is not different from these.

[0097] From the perspective of reducing environmental burden (mainly reducing waste), it is preferred that the crystalline propylene / ethylene block copolymer (A) contains chemically recycled propylene and chemically recycled ethylene. Even if the raw material propylene and / or ethylene contain chemically recycled monomers, since chemically recycled propylene and / or chemically recycled ethylene are monomers obtained by depolymerizing and pyrolyzing polymers such as waste plastics and restoring them to monomer units such as ethylene, and monomers produced using these monomers as raw materials, if the polymer production conditions such as polymerization catalysts, polymerization processes, and polymerization temperatures are the same, the molecular structure is also the same as that of the crystalline propylene / ethylene block copolymer composed of fossil fuel-derived monomers. Therefore, the performance is not different from them.

[0098] <Ethylene polymer (B)> The ethylene polymer (B) of the present invention is an ethylene homopolymer or a copolymer of ethylene and an α-olefin having 4 to 12 carbon atoms, and has a density of 915 to 980 kg / m 3 The melt flow rate (MFR, 190°C, 2.16kg load) measured at a temperature of 190°C and a load of 2.16kg is 0.1-30g / 10min.

[0099] When the ethylene polymer (B) is a copolymer of ethylene and an α-olefin having 4 to 12 carbon atoms, examples of the α-olefin having 4 to 12 carbon atoms include butene-1, pentene-1, hexene-1, heptene-1, octene-1 and decene-1, with butene-1, hexene-1 and octene-1 being preferred.

[0100] When the ethylene-based polymer (B) is a copolymer of ethylene and an α-olefin having 4 to 12 carbon atoms, the content of the structural unit derived from ethylene is 51 mol% or more and less than 100 mol%.

[0101] The density of the ethylene polymer (B) is preferably 910 to 965 kg / m 3 , more preferably 910 to 950 kg / m 3 , more preferably 911 to 945 kg / m 3 The MFR (190° C., 2.16 kg load) of the ethylene polymer (B) is preferably 0.1 to 20 g / 10 min, more preferably 0.5 to 10 g / 10 min, and even more preferably 1 to 9 g / 10 min.

[0102] The ethylene polymer (B) preferably has such MFR and density from the viewpoint of compatibility with the crystalline propylene / ethylene block copolymer (A).

[0103] The ethylene polymer (B) can be produced by homopolymerizing ethylene or copolymerizing ethylene and an α-olefin having 4 to 12 carbon atoms by a conventionally known method, and a commercially available product can also be used.

[0104] <Inorganic filler (C)> The inorganic filler (C) involved in the present invention is not particularly limited, and known inorganic fillers can be used, such as talc, mica, calcium carbonate, barium sulfate, glass fiber, gypsum, magnesium carbonate, magnesium oxide, titanium oxide, iron oxide, and metal powders of zinc, copper, iron, aluminum, etc., or carbon fiber, etc., which can be used alone or in combination. Among them, talc, mica, calcium carbonate, glass fiber, etc. are preferred, and talc is particularly preferred. Regarding the average particle size of talc, it is preferred that the average particle size based on volume measured by laser diffraction is in the range of 1 to 5 μm, preferably 2.5 to 4.5 μm.

[0105] The inorganic filler (C) may be used alone or in combination of two or more.

[0106] <Copolymer rubber (D)> The resin composition of the present invention may contain a copolymer rubber (D) as required in addition to the above-mentioned crystalline propylene / ethylene block copolymer (A), ethylene polymer (B) and inorganic filler (C).

[0107] The copolymer rubber (D) of the present invention is a copolymer of ethylene and an α-olefin having 4 to 12 carbon atoms, and has a density of 850 to 910 kg / m 3The melt flow rate (MFR, 190°C, 2.16 kg load) measured at a temperature of 190°C and a load of 2.16 kg is 0.2 g / 10 min or more and less than 40 g / 10 min.

[0108] Examples of α-olefins having 4 to 12 carbon atoms include butene-1, pentene-1, hexene-1, heptene-1, octene-1, and decene-1, and preferably butene-1, hexene-1, and octene-1. Examples of copolymer rubbers (D) include ethylene / 1-butene random copolymer rubbers, ethylene / 1-hexene random copolymer rubbers, and ethylene / 1-octene random copolymer rubbers, and preferably ethylene / 1-octene random copolymer rubbers or ethylene / 1-butene random copolymer rubbers. Furthermore, two or more ethylene / α-olefin random copolymer rubbers may be used in combination.

[0109] The density of the copolymer rubber (D) is preferably 850 to 895 kg / m 3 , more preferably 855 to 875 kg / m 3 , more preferably 862 to 874 kg / m 3 The MFR (190° C., 2.16 kg load) of the copolymer rubber (D) is preferably 0.2 to 20 g / 10 min, more preferably 0.2 to 10 g / 10 min, and even more preferably 1 to 9 g / 10 min.

[0110] It is preferred that the copolymer rubber (D) has such an MFR and density from the viewpoint of the impact resistance and the like of a molded article formed from the resin composition.

[0111] The copolymer rubber (D) can be produced by copolymerizing ethylene and an α-olefin having 4 to 12 carbon atoms by a conventionally known method, or a commercially available product can be used.

[0112] <Other ingredients (E)> The resin composition of the present invention may contain other component (E) as needed, in addition to the above-mentioned components (A) to (C) and, if necessary, component (D), within a range not impairing the purpose of the present invention.

[0113] As other components (E), various other additives such as nucleating agents, heat stabilizers, antistatic agents, weather stabilizers, light stabilizers, anti-aging agents, antioxidants, fatty acid metal salts, softeners, dispersants, fillers, colorants, lubricants, pigments, etc. can be listed. These additives can be used alone or in combination. When multiple additives are used, the order of mixing the additives is arbitrary, and they can be mixed simultaneously or in a multi-step mixing method such as mixing some components and then mixing other components.

[0114] <Resin composition> In the resin composition of the present invention, when the total amount of the above-mentioned crystalline propylene / ethylene block copolymer (A), ethylene polymer (B), and inorganic filler (C) is taken as 100 parts by mass, the crystalline propylene / ethylene block copolymer (A) is contained in 50 to 94 parts by mass, the ethylene polymer (B) is contained in 1 to 25 parts by mass, and the inorganic filler (C) is contained in 5 to 25 parts by mass. Preferably, in the resin composition of the present invention, when the total amount of the crystalline propylene / ethylene block copolymer (A), ethylene polymer (B), and inorganic filler (C) is taken as 100 parts by mass, the crystalline propylene / ethylene block copolymer (A) is contained in 55 to 89 parts by mass, the ethylene polymer (B) is contained in 1 to 20 parts by mass, and the inorganic filler (C) is contained in 10 to 25 parts by mass. More preferably, the crystalline propylene / ethylene block copolymer (A) is contained in 60 to 84 parts by mass, the ethylene polymer (B) is contained in 1 to 15 parts by mass, and the inorganic filler (C) is contained in 15 to 25 parts by mass.

[0115] Furthermore, the resin composition of the present invention may further contain the above-mentioned copolymer rubber (D). The content of the copolymer rubber (D) is preferably 25 parts by mass or less, more preferably 20 parts by mass or less, further preferably 18 parts by mass or less, and particularly preferably 17 parts by mass or less, relative to a total of 100 parts by mass of the crystalline propylene / ethylene block copolymer (A), the ethylene polymer (B) and the inorganic filler (C). In the case where the resin composition of the present invention contains the copolymer rubber (D), the lower limit of the content of the copolymer rubber (D) is, for example, 0.1 parts by mass, preferably 1 part by mass, and more preferably 2 parts by mass, relative to a total of 100 parts by mass of the crystalline propylene / ethylene block copolymer (A), the ethylene polymer (B) and the inorganic filler (C). When the resin composition of the present invention contains the copolymer rubber (D) in such an amount, the impact resistance of the molded body obtained from the resin composition can be improved.

[0116] The resin composition of the present invention may further contain the above-mentioned other components (E) within the range not impairing the purpose of the present invention. For example, the content of the other components (E) in the resin composition of the present invention is 10 parts by mass or less, preferably 5 parts by mass or less, and more preferably 3 parts by mass or less, relative to 100 parts by mass of the total of the crystalline propylene / ethylene block copolymer (A), the ethylene polymer (B) and the inorganic filler (C).

[0117] The resin composition of the present invention can be produced by mixing the above-mentioned components in a desired mixing ratio.

[0118] Specifically, the resin composition of the present invention can be obtained by simultaneously or stepwise mixing or melt-kneading the above-mentioned crystalline propylene / ethylene block copolymer (A), ethylene polymer (B) and inorganic filler (C), and as required, copolymer rubber (D) and other components (E) using a mixing device such as a Banbury mixer, a single-screw extruder, a twin-screw extruder, or a high-speed twin-screw extruder.

[0119] The properties of the resin composition of the present invention are not particularly limited, but preferably have fluidity suitable for injection molding, preferably a melt flow rate (MFR) measured at a temperature of 230°C and a load of 2.16 kg of 10 to 50 g / 10 min, more preferably 15 to 45 g / 10 min. In addition, the swirl length measured by a specific method in the examples described below is preferably 130 to 160 cm, more preferably 135 to 150 cm.

[0120] The resin composition of the present invention can be molded by a conventionally known molding method for molding a resin composition, thereby producing a molded product. The propylene polymer composition of the present invention is particularly suitable for injection molding, extrusion molding, and the like.

[0121] Such resin composition of the present invention can be applied to various fields such as automobile interior and exterior parts, household appliance parts, food containers, etc. The molded body formed from the resin composition of the present invention exhibits mechanical properties suitable for automobile interior and exterior parts, etc., has particularly excellent rigidity, can suppress the generation of flow marks, and has excellent appearance.

[0122] Molded body The molded article of the present invention is a molded article formed from the above-mentioned resin composition of the present invention. The molded article of the present invention is preferably an injection molded article, an extrusion molded article, or a press molded article, and is more preferably an injection molded article.

[0123] The molded article of the present invention can be applied to various applications. In particular, due to its excellent mechanical properties such as hardness, impact resistance, and rigidity, as well as excellent swirl length characteristics during injection molding, less prone to flow marks, and excellent appearance, it can be applied to automobile parts such as dashboards, door trims, pillars, and other automobile interior parts, and bumpers and other automobile exterior parts.

[0124] As other automobile parts applications, the present invention can be used for automobile exterior parts such as side moldings and aerodynamic floors, outer panel parts such as fenders, door panels, and footboards, and engine peripheral parts such as engine hoods, fans, and fan covers.

[0125] As food containers, for example, the present invention can be used for tableware, bag containers, freezer containers, canned food packages, microwave heat-resistant containers, frozen food containers, cold drink cups, cups, beverage bottles and the like, bag containers, bottle containers and the like.

[0126] Other uses of the molded article of the present invention include, for example, housings of home appliances, wire coating materials, insulators for high-voltage wires, tubes for cosmetics / perfume sprays, medical tubes, infusion tubes, pipes, wiring harnesses, interior materials for motorcycles / railway vehicles / aircrafts / ships, instrument panel surfaces, door interior surfaces, rear window sill decorative surface, ceiling surfaces, rear pillar surfaces, seat back decorative parts, inter-seat storage boxes, armrests, airbag box covers, shift knobs, auxiliary handles, side pedal pads, tilt-adjustable backrest covers, trunk linings, seat belt buckles, interior / exterior moldings, roof moldings, seat belt moldings and other molding materials, door sealing materials, body sealing materials Sealing materials for automobiles, window glass guides, fenders, door corner guards, pedal pads, license plate covers, automobile hose components, ventilation hoses, ventilation duct covers, intake ducts, deflectors, timing belt cover sealing materials, engine hood cushions, door cushions and other automobile interior and exterior materials, vibration-damping tires, brake tires (static tires), racing tires, remote control car tires and other special tires, sealing rings, automobile dust covers, lamp seals, automobile cover materials, rack and pinion covers, timing belts, wiring harnesses, washers, car logos, air filter seals, surface materials for furniture / shoes / clothing / bags / building materials, etc., building seals, waterproof sheets, building material sheets, building material seals pads, window films for building materials, iron core protection components, sealing pads, doors, door frames, window frames, ceiling corners, skirtings, door lintels, etc., floor materials, ceiling materials, wallpapers, health products (such as anti-slip mats / sheets, anti-fall films / pads / sheets), health equipment components, impact absorbing pads, protective gear / protective gear (such as helmets, protective gear), sports products (such as sports handles, protectors), sports protective gear, rackets, mouthguards, balls, golf balls, transportation tools (such as impact absorbing handles for transportation, impact absorbing sheets), vibration-damping pallets, impact absorbing baffles, insulating parts, impact absorbing materials for footwear, impact absorbing foams, impact absorbing films and other impact absorbing materials, grips Holding materials, sundries, toys, midsoles / insoles / outsoles of shoes, sandals, suction cups, toothbrushes, floor materials, gymnastics mats, power tool components, agricultural machinery and equipment components, heat dissipation materials, transparent substrates, sound insulation materials, cushioning materials, wires and cables, shape memory materials, sealing pads, packaging materials for high-temperature treatment such as high-pressure steam sterilization, industrial sealing materials, industrial sewing machine tables, license plate shells, PET bottle cap pads and other cap pads, stationery, office supplies, OA printer brackets, FAX brackets, sewing machine brackets, motor support pads, audio vibration isolation materials and other precision equipment / OA equipment support components, OA heat-resistant pads, clothing boxes, table mats, etc.

[0127] Example The present invention will be described in more detail below based on examples, but the present invention is not limited to these examples.

[0128] (Measurement method and evaluation method) (1) Polymer or resin composition: [Melt flow rate (MFR)] The melt flow rate (MFR) was measured under a load of 2.16 kg in accordance with ASTM D-1238. The measurement temperature was set at 230°C for propylene polymers such as crystalline propylene / ethylene block copolymer (A) and resin compositions containing propylene polymers, and at 190°C for ethylene polymers such as ethylene polymer (B) and copolymer rubber (D).

[0129] [Intrinsic viscosity [η]] About 25 mg of the sample was dissolved in 25 ml of tetralin and the relative viscosity η was measured in an oil bath at 135°C. sp After the tetralin solution was diluted by adding 5 ml of tetralin solvent, the relative viscosity η was measured in the same manner. sp Repeat this dilution operation twice more and find the value of η when the concentration (C) is extrapolated to 0. sp The value of / C is taken as the intrinsic viscosity, and this value is taken as the intrinsic viscosity [η].

[0130] [Ratio of structural units derived from ethylene] The test samples were tested under the following conditions: 13 C-NMR determination.

[0131] ( 13 C-NMR measurement conditions) Measurement device: LA400 nuclear magnetic resonance device manufactured by JEOL Ltd. Measurement mode: BCM (Bilevel Complete decoupling) Observation frequency: 100.4MHz Observation range: 17006.8Hz Pulse width: C core 45° (7.8μs) Pulse repetition time: 5 seconds Sample tube: 5mmφ Sample tube speed: 12Hz Cumulative times: 20,000 times Measuring temperature: 125℃ Solvent: 1,2,4-trichlorobenzene: 0.35ml / deuterated benzene: 0.2ml Sample volume: about 40 mg From the measured spectrum, the ratio of the monomer chain distribution (triad distribution) is determined based on the following document (1), and the molar fraction (mol%) of the structural unit derived from ethylene (hereinafter referred to as E (mol%)) and the molar fraction (mol%) of the structural unit derived from propylene (hereinafter referred to as P (mol%)) in the measured sample are calculated. The ratio (mass %) of the structural unit derived from ethylene in the measured sample (hereinafter referred to as E (mass %)) is calculated from the obtained E (mol%) and P (mol%) according to the following (Formula 1).

[0132] References (1): Kakugo,M.; Naito,Y.; Mizunuma,K.; Miyatake,T., Carbon-13 NMRdetermination of monomer sequence distribution in ethylene-propylenecopolymers prepared with delta-titanium trichloride-diethylaluminum chloride.Macromolecules 1982, 15, (4), 1150-1152 E (mass %) = E (mol %) × 28 × 100 / [P (mol %) × 42 + E (mol %) × 28] (Formula 1) [Melting point] The temperature at the top of the endothermic peak in the third stage was defined as the melting point (Tm) by using a differential scanning calorimeter (DSC, manufactured by Perkin-Elmer Corp. (Diamond DSC)) according to JIS K7121. When there are multiple endothermic peaks, the temperature at the top of the maximum endothermic peak is defined as the melting point (Tm).

[0133] (Measurement conditions) Atmosphere: Nitrogen atmosphere Sample size: 5 mg Sample shape: pressed film (molded at 230°C, thickness 200-400μm) Stage 1: Raise the temperature from 30°C to 240°C at a rate of 10°C / min and hold for 10 minutes.

[0134] Stage 2: Cool down to 60°C at 10°C / min.

[0135] Stage 3: Raise the temperature to 240°C at 10°C / min.

[0136] [Isotactic pentad fraction (mmmm fraction)] It is one of the indicators of the stereoregularity of the polymer. The isotactic pentad fraction (mmmm fraction, %) for studying its microstructure is a value determined by attribution in propylene homopolymers according to Macromolecules 8, 687 (1975) by A. Zambelli et al. 13 C-NMR was measured under the following conditions: isotactic pentad fraction=(peak area at 21.7 ppm) / (peak area at 19 to 23 ppm)×100.

[0137] (Measurement conditions) Device: Bruker BioSpin production AVANCE III cryo-500 NMR device Determination of the core: 13 C (125MHz) Measurement mode: Single pulse proton broadband decoupling Pulse width: 45° (5.00 microseconds) Repeat time: 5.5 seconds Cumulative times: 256 times Measurement solvent: o-dichlorobenzene / deuterated benzene (80 / 20 volume %) mixed solvent Sample concentration: 50mg / 0.6mL Measuring temperature: 120℃ Chemical shift standard: 21.59ppm [Amount of crystalline propylene polymer component and propylene copolymer component] The 23℃ n-decane insoluble part (D insol ) as the crystalline propylene polymer component, and the 23°C n-decane soluble portion (D sol ) as the propylene-based copolymer component, and the amount (mass %) of each component was measured by the following method.

[0138] 200 ml of n-decane was added to 5 g of the sample, and the mixture was heated and dissolved at 145° C. for 30 minutes to obtain a solution (1).

[0139] Next, the solution (1) was cooled to 23°C over about 2 hours and allowed to stand at 23°C for 30 minutes to obtain a solution (2) containing a precipitate (α). Thereafter, the precipitate (α) was filtered out from the solution (2) using a filter cloth having a mesh size of about 15 μm, and after the precipitate (α) was dried, the mass of the precipitate (α) was measured. The value obtained by dividing the mass of the precipitate (α) by the mass of the sample (5 g) was taken as the 23°C n-decane insoluble fraction (D insol ) to determine the amount of crystalline propylene polymer component (mass %).

[0140] In addition, the solution (2) after filtering out the precipitate (α) was added to acetone in an amount of about 3 times that of the solution (2) to precipitate the components dissolved in n-decane, thereby obtaining a precipitate (β). Thereafter, the precipitate (β) was filtered out using a glass filter (G2, mesh size of about 100 to 160 μm), and the mass of the precipitate (β) was measured after drying. The mass of the precipitate (β) was divided by the mass of the sample (5 g) to obtain a value which was taken as the 23°C n-decane soluble portion (D sol ) to determine the amount of propylene-based copolymer component (mass %).

[0141] (2) Evaluation of the molded body: [Flexural modulus] According to JIS K7171, test pieces were prepared from the resin compositions obtained in Examples and Comparative Examples, and the flexural modulus was measured under the following conditions.

[0142] (Measurement conditions) Test piece: 10mm (width) × 80mm (length) × 4.0mm (thickness) Bending speed: 2mm / min Bending span: 64mm [Charpy impact strength] According to JIS K7111, test pieces were prepared from the resin compositions obtained in Examples and Comparative Examples, and the notched Charpy impact strength was measured under the following conditions.

[0143] (Measurement conditions) Temperature: -30℃ and 23℃ Test piece: 10mm (width) × 80mm (length) × 4mm (thickness) The notch is machined.

[0144] [Rockwell hardness] The measurement was carried out using the R scale in accordance with JIS K7202.

[0145] [High-speed surface impact test] At -30°C, an impact shaft with a load cell and a tip diameter of 1 / 2 inch is made to hit a test piece of a square plate with a thickness of 3 mm at a speed of 5 m / s. On the back of the test piece, a table with a tip diameter (support diameter) of 3 inches is used as a support table. From this, the total absorbed energy (J) of the test piece is calculated.

[0146] [Swirl length] A resin flow length measurement mold having a flow path in a cyclone having a thickness of 3 mm and a width of 10 mm was used. The measurement was performed under the following cyclone length measurement injection molding conditions.

[0147] Injection molding machine: J110AD, manufactured by Nippon Steel Co., Ltd. Cylinder temperature: 230℃ Mold temperature: 40℃ Injection time: 10 seconds (no pressure holding setting) [Preparation Example 1] (Preparation of solid titanium catalyst component) According to the preparation method of <Solid titanium catalyst component (i-1)> in Production Example 3 of JP-A-2020-114909, a solid titanium catalyst component containing 1.3 wt% titanium, 20 wt% magnesium, 13.8 wt% diisobutyl terephthalate, and 0.8 wt% diethyl terephthalate was obtained.

[0148] [Preparation Example 2] (Preparation of prepolymerized catalyst) 112.0 g of the solid titanium catalyst component synthesized in Preparation Example 1, 83.0 mL of triethylaluminum, 23.6 mL of diethylaminotriethoxysilane and 10 L of heptane were added to an autoclave with a stirrer having an internal volume of 20 L, the internal temperature was maintained at 15-20 ° C, 672 g of propylene was added, and the mixture was stirred and reacted for 120 minutes. After the polymerization was completed, the solid component was allowed to settle, and the supernatant was removed twice and washed with heptane. The obtained prepolymerized catalyst was suspended again in refined heptane, and heptane was added to adjust the concentration of the solid titanium catalyst component to 0.7 g / L. Each 1 g of the prepolymerized catalyst contained 6 g of polypropylene.

[0149] [Production Example 1] (Production of propylene / ethylene block copolymer (A-1)) <Process (1)> 300 L of propylene was added to the first polymerization vessel with a stirrer having an internal volume of 1000 L. While maintaining the liquid level, propylene was continuously supplied at 118 kg / h, the prepolymerized catalyst obtained in Preparation Example 2 as a solid catalyst component was supplied at 1.2 g / h, triethylaluminum was supplied at 13.3 mL / h, diethylaminotriethoxysilane was supplied at 5.1 mL / h, and hydrogen was supplied in such a manner that the hydrogen concentration in the gas phase reached 6.6 mol%. The polymerization was carried out at a temperature of 73.5°C, a pressure of 3.39 MPa-G, and an average residence time of 1.1 hours.

[0150] The obtained slurry was sent to a 500 L internal volume agitator pressure type second polymerization reactor for further polymerization. In the second polymerization reactor, 300 L of propylene was added, and while maintaining the liquid level, propylene was continuously supplied at 14.5 kg / h, dicyclopentadienyltitanium dichloride was supplied at 3.2 g / h, and hydrogen was supplied in such a manner that the hydrogen concentration in the gas phase reached 7.3 mol%. The polymerization was carried out at a temperature of 73.5°C, a pressure of 3.27 MPa-G, and an average residence time of 1.0 hour to obtain a propylene homopolymer (H-1).

[0151] <Process (2A)> The obtained slurry of the propylene homopolymer (H-1) was fed to the third pressure-type polymerization reactor with an internal volume of 500 L and equipped with an agitator for further polymerization. In the third polymerization reactor, 260 L of propylene was added, and while maintaining the liquid level, propylene was continuously supplied at 16.9 kg / h, ethoxyethoxyethyl acetate as an activity regulator was supplied at 0.28 ml / h, ethylene was supplied in such a manner that the concentration of ethylene dissolved in the propylene liquid phase reached 0.198 mol relative to 1 mol of propylene, and hydrogen was supplied in such a manner that the hydrogen concentration in the gas phase reached 5.9 mol%. The polymerization was carried out at a temperature of 53.2°C, a pressure of 3.24 MPa-G, an average residence time of 0.75 hours, and an ethylene concentration in the gas phase of 29.1 mol%, to obtain a block copolymer (B-1).

[0152] <Process (2B)> The obtained copolymer slurry containing the block copolymer (B-1) was fed to the fourth polymerizer with a stirrer having an internal volume of 500 L for further polymerization. In the fourth polymerizer, 260 L of propylene was added, and while maintaining the liquid level, propylene was continuously supplied at 52.1 kg / h, dicyclopentadienyl titanium dichloride was supplied at 35.2 mg / h, ethylene was supplied in such a manner that the concentration of ethylene dissolved in the propylene liquid phase reached 0.129 mol relative to 1 mol of propylene, and hydrogen was supplied in such a manner that the hydrogen concentration in the gas phase reached 0.16 mol%, and polymerization was carried out. The temperature at this time was 60.4°C, the pressure was 3.16 MPa-G, the average residence time was 0.55 hours, and the ethylene concentration in the gas phase was 19.7 mol%.

[0153] The obtained slurry was subjected to a deactivation treatment, gasified, and then subjected to gas-solid separation, and vacuum dried at 80° C. Thus, a propylene / ethylene block copolymer (A-1) was obtained.

[0154] The properties of the obtained propylene homopolymer (H-1), block copolymer (B-1) and propylene-ethylene block copolymer (A-1) are as follows.

[0155] ・Propylene homopolymer (H-1) Intrinsic viscosity [η] = 0.78 dl / g MFR (2.16kg load, 230℃) = 240g / 10min Isotactic pentad fraction (mmmm fraction) = 98.1 mol% ・Block copolymer (B-1) Intrinsic viscosity [η] = 1.04 dl / g MFR (2.16kg load, 230℃) = 127g / 10min Ethylene content = 13.0 mass% Ratio of 23°C n-decane soluble part = 16.7 mass% Ethylene content of n-decane soluble fraction at 23°C = 53.6 mol% The intrinsic viscosity of the n-decane soluble part at 23℃[η]=2.1dl / g ・Propylene-ethylene block copolymer (A-1) Intrinsic viscosity [η] = 1.39 dl / g MFR (2.16kg load, 230℃) = 54g / 10min Ethylene content = 15.4 mass% Ratio of 23°C n-decane soluble part = 19.3 mass % Ethylene content of n-decane soluble fraction at 23°C = 52.3 mol% The intrinsic viscosity of the n-decane soluble part at 23℃[η]=3.3dl / g The properties of the propylene / ethylene block copolymer (A-1) determined based on these properties are shown in Table 1. The propylene polymer component (PP-1) is regarded as a 23°C n-decane insoluble portion, and the propylene copolymer components (EP-1) and (EP-2) are regarded as a 23°C n-decane soluble portion.

[0156] [Comparative Production Example 1] (Production of Polymer Mixture (A'-1)) <Production of block copolymer (a-1)> To a tubular polymerizer having an internal volume of 8 L, propylene was continuously supplied at 20 kg / h, hydrogen was supplied at 0.5 NL / h, the prepolymerized catalyst obtained in Preparation Example 2 was supplied at 0.38 g / h as a solid catalyst component, triethylaluminum was supplied at 2.1 mL / h, and diethylaminotriethoxysilane was supplied at 1.6 mL / h, and polymerization was carried out in a liquid-full state without the presence of a gas phase. The temperature of the tubular polymerizer was 16° C. and the pressure was 3.6 MPa-G.

[0157] The obtained slurry was fed to a tubular polymerization reactor with an internal volume of 58 L for further polymerization. Propylene was continuously supplied at 23 kg / h and hydrogen was supplied at 172 NL / h to the polymerization reactor at a temperature of 70° C., a pressure of 3.6 MPa-G, and an average residence time of 0.61 hours.

[0158] The obtained slurry was fed into a pressure polymerization reactor with an internal volume of 70 L and equipped with an agitator for further polymerization. Propylene was continuously supplied to the polymerization reactor at 45 kg / h, and hydrogen was supplied in such a manner that the hydrogen concentration in the gas phase reached 9.6 mol%. The polymerization was carried out at a temperature of 68.0°C, a pressure of 3.2 MPa-G, and an average residence time of 0.35 hours to obtain a propylene homopolymer (h-1).

[0159] The obtained slurry was transferred to a pipette with an internal volume of 2.4 L, and an activity regulator (ADMER163, produced by Croda Japan) and an anti-adhesion agent (L-71 (trade name), produced by ADEKA) were supplied at 1.83 g / h and 0.51 g / h in the transfer pipe to contact the slurry. The contacted slurry was gasified and subjected to gas-solid separation, and then a powder of a propylene homopolymer (h-1) was fed to a gas phase polymerizer with an internal volume of 480 L in such a manner that the powder amount reached 12.4 kg. Thereafter, propylene, ethylene, and hydrogen were continuously supplied in such a manner that the gas composition in the gas phase polymerizer reached ethylene / (ethylene+propylene)=0.3295 (molar ratio) and hydrogen / ethylene=0.1460 (molar ratio), and polymerization was carried out at a temperature of 70°C, a pressure of 1.2 MPa-G, and a residence time of 0.68 hours.

[0160] Thereafter, gas-solid separation was performed and vacuum drying was performed at 80° C. to obtain a block copolymer (a-1) as a blending polymer. The properties of the obtained homopolypropylene (h-1) and block copolymer (a-1) are as follows.

[0161] ・Propylene homopolymer (h-1) Intrinsic viscosity [η] = 0.74 dl / g MFR (2.16kg load, 230℃) = 252g / 10min Isotactic pentad fraction (mmmm fraction) = 98.2 mol% ・Block copolymer (a-1) Intrinsic viscosity [η] = 0.94 dl / g MFR (2.16kg load, 230℃) = 90g / 10min Ethylene content = 15.1 mass% Ratio of 23°C n-decane soluble part = 19.5 mass% Ethylene content of n-decane soluble fraction at 23°C = 53 mol% The intrinsic viscosity of the n-decane soluble part at 23℃[η]=2.1dl / g <Production of block copolymer (a-2)> To a tubular polymerizer with an internal volume of 8 L, propylene was continuously supplied at 20 kg / h, hydrogen was supplied at 0.5 NL / h, the prepolymerized catalyst obtained in Preparation Example 2 was supplied at 0.30 g / h as a solid catalyst component, triethylaluminum was supplied at 1.7 mL / h, and diethylaminotriethoxysilane was supplied at 1.3 mL / h, and polymerization was carried out in a liquid-full state without the presence of a gas phase. The temperature of the tubular polymerizer was 16°C and the pressure was 3.2 MPa-G. The obtained slurry was sent to a tubular polymerizer with an internal volume of 58 L for further polymerization. To the polymerizer, propylene was continuously supplied at 23 kg / h and hydrogen was supplied at 172 NL / h, the temperature was 63°C, the pressure was 3.2 MPa-G, and the average residence time was 0.60 hours.

[0162] The obtained slurry was fed into a pressure polymerization reactor with an internal volume of 70 L and equipped with an agitator for further polymerization. Propylene was continuously supplied to the polymerization reactor at 45 kg / h, and hydrogen was supplied in such a manner that the hydrogen concentration in the gas phase reached 9.5 mol%. The polymerization was carried out at a temperature of 62.0°C, a pressure of 2.8 MPa-G, and an average residence time of 0.35 hours to obtain a propylene homopolymer (h-2).

[0163] The obtained slurry was transferred to a pipette with an internal volume of 2.4 L, and an anti-adhesion agent (L-71 (trade name), produced by ADEKA) was supplied in the transfer pipe at 0.32 g / h to contact the slurry. The contacted slurry was gasified and subjected to gas-solid separation, and then a powder of a propylene homopolymer (h-2) was fed to a gas phase polymerizer with an internal volume of 480 L in such a manner that the powder amount reached 20.6 kg. Thereafter, propylene, ethylene, and hydrogen were continuously supplied in such a manner that the gas composition in the gas phase polymerizer reached ethylene / (ethylene + propylene) = 0.158 (molar ratio) and hydrogen / ethylene = 0.0030 (molar ratio). The polymerization temperature was set to 75°C, the pressure was set to 1.6 MPa-G, and the residence time was set to 1.42 hours to carry out polymerization.

[0164] Thereafter, gas-solid separation was performed, and vacuum drying was performed at 80° C. to obtain a block copolymer (a-2). The properties of the obtained propylene homopolymer (h-2) and block copolymer (a-2) are as follows.

[0165] ・Propylene homopolymer (h-2) Intrinsic viscosity [η] = 0.77 dl / g MFR (2.16kg load, 230℃) = 250g / 10min Isotactic pentad fraction (mmmm fraction) = 98.2 mol% ・Block copolymer (a-2) Intrinsic viscosity [η] = 4.06 dl / g MFR (2.16kg load, 230℃) = 0.8g / 10min Ethylene content = 23.8 mass% Ratio of 23°C n-decane soluble part = 39.7 mass% Ethylene content of n-decane soluble fraction at 23°C = 45 mol% The intrinsic viscosity of the n-decane soluble part at 23℃[η]=8.0dl / g <Production of polymer mixture (A'-1)> 83 parts by mass of the block copolymer (a-1) obtained above, 7.8 parts by mass of the block copolymer (a-2), 9.2 parts by mass of a propylene homopolymer (PRIMEPOLYPRO (registered trademark) J137G (trade name), manufactured by Primen Polymer Co., Ltd.), 0.1 parts by mass of calcium stearate (manufactured by NOF Corporation), and 0.1 parts by mass of IRGANOX (registered trademark) 1010 (manufactured by BASF Japan Ltd.), 0.1 parts by mass of IRGAFOS 168 (manufactured by BASF Japan Ltd.), and 0.1 parts by mass of H-BHT (manufactured by Honshu Chemical Industry Co., Ltd.) as antioxidants were added and dry blended using a tumbler mixer. Then, the mixture was melt-kneaded in a twin-screw extruder (NR-II, co-rotating twin-screw extruder manufactured by Nakatani Machinery Co., Ltd.) at a barrel temperature (kneading temperature) of 190° C., a screw speed of 200 rpm, and an extrusion rate of 20 kg / h to obtain a polymer mixture (A′-1).

[0166] Table 1 shows the properties of the polymer mixture (A′-1) determined based on the properties of the propylene homopolymer (h-1) and the like described above.

[0167]

Table 1

[0168] [Example 2] In addition to adjusting the amount of the ethylene polymer (B-1) in Example 1 to 10 parts by mass, a copolymer rubber (D) (ethylene / 1-octene copolymer (EOR), manufactured by Dow Chemical Company, ENGAGE 8200 (MFR (190° C., 2.16 kg) = 5.0 g / 10 min, density 870 kg / m 3 The same operation as in Example 1 was performed except that 4 parts by weight of )) was used to prepare pellets and test pieces of the resin composition, and the evaluation was performed. The evaluation results are shown in Table 2.

[0169] [Example 3] In addition to adjusting the amount of the ethylene polymer (B-1) in Example 1 to 7 parts by mass, a copolymer rubber (D) (ethylene / 1-octene copolymer (EOR), manufactured by Dow Chemical Company, ENGAGE 8200 (MFR (190° C., 2.16 kg) = 5.0 g / 10 min, density 870 kg / m 3 The same operation as in Example 1 was performed except that 7 parts by weight of )) was used to prepare pellets and test pieces of the resin composition, and the evaluation was performed. The evaluation results are shown in Table 2.

[0170] [Example 4] In addition to adjusting the amount of the ethylene polymer (B-1) in Example 1 to 4 parts by mass, a copolymer rubber (D) (ethylene / 1-octene copolymer (EOR), manufactured by Dow Chemical Company, ENGAGE 8200 (MFR (190° C., 2.16 kg) = 5.0 g / 10 min, density 870 kg / m 3 The same operation as in Example 1 was performed except that 10 parts by weight of )) was used to prepare pellets and test pieces of the resin composition, and the evaluation was performed. The evaluation results are shown in Table 2.

[0171] [Example 5] In addition to adjusting the amount of the ethylene polymer (B-1) in Example 1 to 2 parts by mass, a copolymer rubber (D) (ethylene / 1-octene copolymer (EOR), manufactured by Dow Chemical Company, ENGAGE 8200 (MFR (190° C., 2.16 kg) = 5.0 g / 10 min, density 870 kg / m 3 The same operation as in Example 1 was performed except that 12 parts by weight of )) was used to prepare pellets and test pieces of the resin composition, and the evaluation was performed. The evaluation results are shown in Table 2.

[0172] [Comparative Example 1] The same procedure as in Example 3 was carried out except that 65 parts by mass of the propylene-based block copolymer (A-1) was replaced with 65 parts by mass of the polymer mixture (A′-1) to produce pellets and test pieces of the resin composition, and the evaluation was performed.

[0173] [Comparative Example 2] The same procedure as in Example 1 was carried out except that 14 parts by mass of the ethylene polymer (B-1) was replaced with 14 parts by mass of the copolymer rubber (D) to produce pellets and test pieces of the resin composition, and the evaluation was performed.

[0174]

Table 2

[0175] [Example 7] The ethylene polymer (B-1) in Example 3 was replaced by 7 parts by mass of an ethylene polymer (B-3) (Evolue SP4020 (MFR (190°C, 2.16 kg) = 1.8 g / 10 min, density 937 kg / m 3 )) Except for the above, pellets and test pieces of the resin composition were prepared in the same manner as in Example 3 and evaluated. The evaluation results are shown in Table 3.

[0176] [Example 8] The above-mentioned reaction mixture was prepared by replacing 7 parts by mass of the ethylene polymer (B-1) in Example 3 with 7 parts by mass of an ethylene polymer (B-4) (produced by DuPont-MITSUI POLYCHEMICALS Co., Ltd., MIRASON 11P (MFR (190°C, 2.16 kg) = 7.2 g / 10 min, density 917 kg / m 3 )) Except for the above, pellets and test pieces of the resin composition were prepared in the same manner as in Example 3 and evaluated. The evaluation results are shown in Table 3.

[0177] [Comparative Example 3] The same procedure as in Example 6 was carried out except that 65 parts by mass of the propylene-based block copolymer (A-1) was used instead of 65 parts by mass of the polymer mixture (A′-1) to produce pellets and test pieces of the resin composition and evaluate them.

[0178] [Comparative Example 4] The same procedure as in Example 8 was carried out except that 65 parts by mass of the propylene block copolymer (A-1) was replaced with 65 parts by mass of the polymer mixture (A′-1) to produce pellets and test pieces of the resin composition, and the evaluation was performed.

[0179]

Table 3

Claims

1. A resin composition, characterized in that contain: 50 to 94 parts by weight of a crystalline propylene / ethylene block copolymer (A) satisfying the following conditions 1 to 3; Density is 915~980kg / m 3 , and 1 to 25 parts by weight of an ethylene polymer (B) having a melt flow rate of 0.1 to 30 g / 10 min as measured at a temperature of 190° C. and a load of 2.16 kg, wherein the ethylene polymer (B) is an ethylene homopolymer or a copolymer of ethylene and an α-olefin having 4 to 12 carbon atoms; and Inorganic filler (C) 5 to 25 parts by weight, Here, the total amount of the crystalline propylene / ethylene block copolymer (A), the ethylene polymer (B), and the inorganic filler (C) is taken as 100 parts by mass. Condition 1: A block copolymer composed of a crystalline propylene polymer component and a propylene copolymer component, wherein the amount of the propylene copolymer component is 10 to 50% by mass, the intrinsic viscosity [η] of the propylene copolymer component measured in tetralin at 135°C is 2.0 to 6.0 dl / g, and the proportion of the structural unit derived from ethylene in the propylene copolymer component is 30 to 80 mol%. Condition 2: The propylene-based copolymer component contains a copolymer component EP-1 and a copolymer component EP-2, The copolymer component EP-1 is a component containing 40 to 80 mol% of structural units derived from ethylene and having an intrinsic viscosity [η] of 1.5 to 4.0 dl / g as measured in tetralin at 135°C. The copolymer component EP-2 is a component containing 30 to 50 mol% of structural units derived from ethylene and having an intrinsic viscosity [η] of 5.0 to 10 dl / g as measured in tetralin at 135°C. Condition 3: The mass ratio of the copolymer component EP-1 to the copolymer component EP-2 (EP-1 / EP-2) is 10 / 1 to 1 / 1.

2. The resin composition according to claim 1, characterized in that The copolymer component EP-1 contains 51 to 58 mol% of structural units derived from ethylene. The copolymer component EP-2 contains 38 to 48 mol% of structural units derived from ethylene.

3. The resin composition according to claim 1, characterized in that The crystalline propylene / ethylene block copolymer (A) further satisfies the following conditions 4 to 6: Condition 4: The melt flow rate measured at a temperature of 230°C and a load of 2.16 kg is 1 to 500 g / 10 min. Condition 5: The melting point measured by differential scanning calorimetry is 155-170°C, Condition 6: Utilization of the crystalline propylene polymer component 13 The isotactic pentad component rate measured by C-NMR is 96.0-99.9%.

4. The resin composition according to claim 1, characterized in that The crystalline propylene / ethylene block copolymer (A) further satisfies at least one of the following conditions 7 and 8, Condition 7: The difference ΔC2 between the content of the structural unit derived from ethylene in the copolymer component EP-1 and the content of the structural unit derived from ethylene in the copolymer component EP-2 is 1.0 to 13 mol%. Condition 8: The difference Δη between the intrinsic viscosity [η] of the copolymer component EP-1 measured in tetralin at 135°C and the intrinsic viscosity [η] of the copolymer component EP-2 measured in tetralin at 135°C is 5.8 to 8.5 dl / g.

5. The resin composition according to claim 1, characterized in that The present invention further comprises 25 parts by mass or less of a copolymer rubber (D) based on 100 parts by mass of the total of the crystalline propylene / ethylene block copolymer (A), the ethylene polymer (B) and the inorganic filler (C), The copolymer rubber (D) is a copolymer of ethylene and an α-olefin having 4 to 12 carbon atoms and has a density of 850 to 910 kg / m 3 , the melt flow rate measured at a temperature of 190°C and a load of 2.16 kg is greater than 0.2 g / 10 min and less than 40 g / 10 min. 6 . A molded body formed from the resin composition according to claim 1 .

7. The molded article according to claim 6, wherein The molded body is an injection molded body.

8. The molded article according to claim 6, wherein The molded body is an automobile part.

9. The molded article according to claim 8, wherein The automobile part is a bumper.

Citation Information

Patent Citations

  • Catalyst for polymerizing olefin, transition metal compound, polymerization of olefin and alpha-olefin-conjugated diene copolymer

    JP1999315109A

  • Polypropylene resin composition and its molded item

    JP2007092049A

  • Polypropylene resin composition and molded body

    JP2008239971A

  • Microporous film comprising propylene polymer composition

    JP2020114909A

  • Metallocene compound, process for producing metallocene compound, olefin polymerization catalyst, process for producing polyolefin, and polyolefin

    WO2001027124A1